Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1021/jf050448p
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in Vitro Estrogenic Activities of Compounds from Hops (Humulus lupulus) and Red Clover (Trifolium pratense)

Abstract: Since the prevailing form of hormone replacement therapy is associated with the development of cancer in breast and endometrial tissues, alternatives are needed for the management of menopausal symptoms. Formulations of Trifolium pratense L. (red clover) are being used to alleviate menopauseassociated hot flashes but have shown mixed results in clinical trials. The strobiles of Humulus lupulus L. (hops) have been reported to contain the prenylflavanone, 8-prenylnaringenin (8-PN) as the most estrogenic constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 54 publications
8
115
1
Order By: Relevance
“…(5). These results are consistent with previously reported screening studies of hop extracts [18], which found that 8-prenylnaringenin was the most potent estrogen in hop extracts.…”
Section: Screening Of Botanical Extractssupporting
confidence: 93%
See 1 more Smart Citation
“…(5). These results are consistent with previously reported screening studies of hop extracts [18], which found that 8-prenylnaringenin was the most potent estrogen in hop extracts.…”
Section: Screening Of Botanical Extractssupporting
confidence: 93%
“…Centrifugal ultrafiltration filters (Microcon YM-30) were purchased from Millipore (Bedford, MA). Ethanolic extracts of the aerial parts of red clover, Trifolium pratense L., and hop cones, from Humulus lupulus L., were prepared as described previously [18].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 8-PN and IX were also evaluated since 8-PN is the major active phytoestrogen in H. lupulus [16,17,20,21], and IX can be metabolized to 8-PN [22]. The major phytoestrogens in T. pratense, daidzein and genistein, and their metabolic precursors, formononetin and biochanin A, were not evaluated since there is already a large body of data on these compounds [36,37], and the primary focus was on H. lupulus.…”
Section: Discussionmentioning
confidence: 99%
“…The most potent estrogen in H. lupulus is 8-PN, which is in actuality an artifact formed through isomerization of the precursor chalcone, desmethylxanthohumol [18,19]. 8-Prenylnaringenin has been shown in a variety of in vitro assays to be estrogenic in the nanomolar range [16,17,20,21]. It can also be formed from precursors such as IX, and xanthohumol (XH), through metabolism [22].…”
mentioning
confidence: 99%
“…Secondary metabolites are known for their strong biological activity, including improvement of quality of both human and animal diet. It is known that red clover isoflavones are used in HRT, for the prevention of diseases that occur in menopause in women (Overk et al, 2005). In the study by Oleszek et al (2007) it was discovered that the species T. heldreichianum, T. scabrum and T. subterraneum have extremely high content of isoflavones (more than red clover), which indicates the necessity of studying the representatives of this genus in wild flora.…”
Section: Introductionmentioning
confidence: 99%